Three Essays in Macroeconomics - Khan, Shahed Kaiser (My University, 2018)
This thesis contains three chapters on topics in macroeconomics. Chapter 1 explains why unemployment is more persistent than average hours worked following a financial crisis. Chapter 2 assesses the performance of different monetary policy rules in stabilizing macroeconomic fluctuations in response to adverse financial shocks. Chapter 3 studies the links between U.S. monetary policy uncertainty and the default incentives of emerging nations' governments.